Prospective Comparison of Angio-Seal versus Manual Compression for Hemostasis after Neurointerventional Procedures under Systemic Heparinization - Wong, H.-F.; Lee, C.-W.; Chen, Y.-L.; Wu, Y.-M.; Weng, H.-H.; Wang, Y.-H.; Liu, H.-M. (American Journal of Neuroradiology, 2013)
BACKGROUND AND PURPOSE: The use of arterial closure device in patients with prolonged high ACT values has not been extensively studied. The aim of this study was to compare the safety and efficacy of an arterial closure device, Angio-Seal, with manual compression in patients on anticoagulation following neurointerventional procedures. MATERIALS AND METHODS: This was a 2-center prospective study approved by our institutional review boards. In total, 153 consecutive patients with 174 arteriotomies (86 men, 67 women; mean age, 56.1 ± 16.2 years) following femoral arterial puncture for neurointerventional procedures were enrolled in convenience sampling. All of the patients were systemically heparinized with an ACT between 250 and 500 seconds before removal of the sheath after the procedure. Group 1 consisted of 104 arteriotomies that were closed with an arterial closure device (Angio-Seal), and group 2 consisted of 70 arteriotomies treated with manual compression. The ACT before sheath removal, time to hemostasis, and complications immediately and 24 hours after the procedure were recorded. RESULTS: The mean ACT before sheath removal was 284.8 ± 37.6 seconds (range, 250–414 seconds). The mean hemostasis time was significantly shorter in group 1 (2.4 ± 11.7 minutes) compared with group 2 (44.7 ± 27.4 minutes) (95% CI, 38.16–51.24 minutes; P < .001). Hematoma occurred in 9 patients in group 1 (8.6%) and 18 in group 2 (25.7%). One patient developed an arterial occlusion after hemostasis with the closure device, but this was successfully revascularized. CONCLUSIONS: Angio-Seal was found to safely and effectively achieve rapid closure of the femoral access site in patients undergoing neuroendovascular procedures under systemic heparinization with an ACT in the range of 250–500 seconds. ACTactivated clotting timeCIconfidence intervalORodds ratio